A Randomized Trial of Methadone Initiation Prior to Release from Incarceration - McKenzie, Michelle (2012)
Individuals who use heroin and illicit opioids are at high risk for infection with human immunodeficiency virus (HIV) and other blood-borne pathogens, as well as incarceration. The purpose of the randomized trial reported here is to compare outcomes between participants who initiated methadone maintenance treatment (MMT) prior to release from incarceration, with those who were referred to treatment at the time of release. Participants who initiated MMT prior to release were significantly more likely to enter treatment postrelease (P < .001) and for participants who did enter treatment, those who received MMT prerelease did so within fewer days (P = .03). They also reported less heroin use (P = .008), other opiate use (P = .09), and injection drug use (P = .06) at 6 months. Initiating MMT in the weeks prior to release from incarceration is a feasible and effective way to improve MMT access postrelease and to decrease relapse to opioid use.